Anesthetic management of parturients with Arnold Chiari malformation-I: a multicenter retrospective study. (February 2019) - Gruffi, T.R.; Peralta, F.M.; Thakkar, M.S.; Arif, A.; Anderson, R.F.; Orlando, B.; Coffman, J.C.; Nathan, N.; McCarthy, R.J.; Toledo, P.; Habib, A.S.
Highlights: Arnold-Chiari malformation was diagnosed after delivery in 20% of our cohort. Neuraxial and general anesthetics were administered with few complications. Catastrophic neurological outcomes were not observed. Abstract: Background: Consensus regarding the safest mode of delivery and anesthetic management for parturients with Arnold Chiari malformation-I (ACM-I) remains controversial. This study assessed their anesthetic management and reported anesthetic complications during hospitalization for delivery. Methods: This was a multicenter, retrospective, cohort study of patients with ACM-I undergoing vaginal or cesarean delivery. Data were obtained from the electronic databases of four United States academic institutions using International Classification of Diseases (ICD) codes from 2007–2017 at three sites and 2004–2017 at one site. The primary outcome was anesthetic complications. Results: Data were analyzed for 185 deliveries in 148 patients. Diagnosis of ACM-I was made prior to delivery in 147 (80%) cases. Pre-delivery neurosurgical consultation for management of ACM-I was performed in 53 (36%) patients. Pre-existing symptoms were recorded for 89 (48%) of the deliveries. Vaginal deliveries occurred in 80 (43%) cases, and 62 women (78%) received neuraxial labor analgesia. Cesarean delivery was performed in 105 (57%) cases, of which 70 women (67%) had neuraxial anesthesia and 34 (32%) received general anesthesia. Post-dural puncture headache was reported in three (2%) patients who had neuraxial anesthesia, and in two (12%) patients with syringomyelia. There was one (3%) reported case of aspiration pneumonia with general anesthesia. Conclusions: The findings suggest that anesthetic complications occur infrequently in patients with ACM-I regardless of the anesthetic management. Although institutional preference in anesthetic and obstetric care appears to drive patient management, the findings suggest that an individualized approach has favorable outcomes in this population.